Schools food environments in Boukombe and Natitingou and students' perception about these environments - Houndolo, Melina Maureen; Bodjrenou, Fifali Ulrich Sam; BANKOLE, Bissola Malikath; Jordan, Irmgard; Termote, Celine; Amoussa Hounkpatin, Waliou (2023)
The food environment is recognized as having a very strong influence on the eating habits of individuals and students. This study aimed at analyzing the food environment around Boukombe and Natitingou's main colleges and the students' perception about this environment.